YouTube™ video content analysis on space maintainers - Hakan Yilmaz; Merve Nur Aydin (Wolters Kluwer Medknow Publications, 2020)
Aim: Since it is difficult to understand by patients or parents, YouTube™ videos can be used to describe space maintainers. However, the reliability and quality of the information in the YouTube™ videos about space maintainers have not been investigated. Therefore, the purpose of this study was to examine the quality of information provided on YouTube™ about space maintainers. Materials and Methods: Videos were searched on YouTube™ using the key words of "space maintainers" in the Google Trends application. From the first 120 results, after discarding the ones immediately deemed insufficient, 46 videos were selected for analysis. To classify the video content as high or low, a scoring system formed of seven parameters was used. For a global evaluation of the video quality, the video information and quality index were applied. Data obtained were analyzed statistically using the independent t-test, the Mann-Whitney U-test, and the Chi-square test, and the Pearson correlation coefficient was calculated. Results: The quality of the content of videos was found to be mean 2.89 from a maximum of seven points, with 15 (32.6%) videos determined to be of high quality and 31 (67.4%) of low quality. The "likes" index was higher in the high-quality videos (P < 0.05). No statistically significant difference was determined between the groups responsible for uploading videos to YouTube™ in respect of the quality content (P > 0.05). Conclusion: The content quality of videos on YouTube™ about space maintainers is usually low. High-quality content expected from videos uploaded by specialists/dental practitioners was not provided compared to other groups.